2001
DOI: 10.2337/diacare.24.7.1181
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to a 38-kDa Glycosylated Islet Cell Membrane–Associated Antigen in (Pre)type 1 Diabetes

Abstract: THE BELGIAN DIABETES REGISTRY 6OBJECTIVE -To study the association of autoantibodies against a 38-kDa glycated islet cell membrane-associated (GLIMA) protein with (pre)type 1 diabetes, patient characteristics, and other immune and genetic markers of the disease and to evaluate the possible added value of GLIMA antibody determinations for disease prediction and classification.RESEARCH DESIGN AND METHODS -Recent-onset type 1 diabetic patients (n ϭ 100), prediabetic siblings (n ϭ 23), and nondiabetic control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Several studies have shown elevated glycation of pancreatic b proteins, including insulin, accompanying T1D (McKillop et al 2002). Although some studies suggest the presence of antibodies to AGE in T1D patients and animals (Turk et al 2001;Winnock et al 2001;Nicoloff et al 2002), as yet no CD4 þ T-cell epitopes have been reported to contain a glycated amino acid.…”
Section: Autoantigens Created By Posttranslational Modifications In Tmentioning
confidence: 99%
“…Several studies have shown elevated glycation of pancreatic b proteins, including insulin, accompanying T1D (McKillop et al 2002). Although some studies suggest the presence of antibodies to AGE in T1D patients and animals (Turk et al 2001;Winnock et al 2001;Nicoloff et al 2002), as yet no CD4 þ T-cell epitopes have been reported to contain a glycated amino acid.…”
Section: Autoantigens Created By Posttranslational Modifications In Tmentioning
confidence: 99%
“…Two reports estimate the prevalence of glima 38 autoantibodies, measured by complex immuno-precipitation assays of radio-labelled cell lines, to be around 20 to 40% in patients with type 1 diabetes [1,3]. The recent identification of glima 38 as tetraspanin 7 [4] allows the development of less cumbersome recombinant protein-based immunoassays for the measurement of these autoantibodies.…”
Section: Introductionmentioning
confidence: 99%
“…detected by a modification of immunoprecipitation assays previously described (13)(14)(15) using the neuronal mouse cell line GT1.7 as source of antigen. Endogenous proteins in GT1.7 cells were labeled by incubation in methionine-free DMEM medium containing 4 MBq/ml 35 S-methionine for 7 h at 37°C.…”
Section: Screen Of Type 1 Diabetic Patient Sera For Glima Antibodiesmentioning
confidence: 99%
“…Four major humoral autoantigens have been identified in Type 1 diabetes by defining the specificity of autoantibodies in the disease: insulin (9), glutamate decarboxylase (10), IA-2 (11), and zinc transporter-8 (ZnT8) (12). Autoantibodies to a fifth, a 38kDa glycosylated membrane protein (Glima), have been detected in 19-38% of Type 1 diabetic patients, with significantly higher prevalence (up to 50%) in children (13)(14)(15). The molecular identity of Glima has for many years proved elusive, hampering the characterization of autoimmunity to the protein and the development of sensitive, specific autoantibody assays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation